The research of EM wave absorbing properties of ferrite/silicon carbide/graphite three-layer composite coating knitted fabrics. Issue 4 (2nd April 2016) - Liu, Yuanjun; Zhao, Xiaoming; Tuo, Xiao
Abstract : The polyester knitted fabric was used as a basilicon carbide structure material. A three-layer composite coating finishing was applied to the structure material using ferrite, silicon carbide, and graphite absorbing materials. The single factor test method was used in this series of research. The impact on dielectric constant and loss tangent of absorbtion of each agent and the coating thickness of each layer were studied. From these results, the three-layer composite coating materials that had excellent absorbing properties were selected and prepared. The results showed that when the ferrite (60 wt%) was used as a bottom layer, the silicon carbide (36 wt%) was used as a middle layer and the graphite (24 wt%) was used as a surface layer with the respective thickness of 0.5, 0.3, and 0.3 mm, an excellent microwave absorbing property was noted for the three-layer composite coating material. In order to meet the requirements for the engineering field, physilicon carbideal and mechanical properties of the microwave absorbing materials were also characterized.